Against the Odds - Dyson, James (Texere LLC, 2002)
How did a maverick English inventor manage to design, market and make money from his own invention, toppling market leaders in the process? This inspirational autobiography tells the remarkable story behind James Dyson and his most successful invention to date Â- the Dual Cyclone. This revolutionary (bagless) vacuum cleaner has taken the market by storm, but not without years of personal struggle and crises for its inventor. Faced with little or no support at every turn, DysonÂ's extraordinary story shows how his unswerving optimism and self-belief has brought him spectacular success